Recent advances in polydopamine-coated metal–organic frameworks for cancer therapy - He, Jingchao; Wang, Guangtian; Zhou, Yongfang; Li, Bin; Shang, Pan (Frontiers in Bioengineering and Biotechnology, 2025)
The creation and development of classical multifunctional nanomaterials are crucial for the advancement of nanotherapeutic treatments for tumors. Currently, metal–organic frameworks (MOFs) modified with polydopamine (PDA) are at the forefront of nanomedicine research, particularly in tumor diagnostics and therapy, owing to their exceptional biocompatibility, expansive specific surface area, multifaceted functionalities, and superior photothermal properties, which led to significant advancements in anti-tumor research. Consequently, a range of anti-cancer strategies has been devised by leveraging the exceptional capabilities of MOFs, including intelligent drug delivery systems, photodynamic therapy, and photothermal therapy, which are particularly tailored for the tumor microenvironment. In order to gain deeper insight into the role of MOFs@PDA in cancer diagnosis and treatment, it is essential to conduct a comprehensive review of existing research outcomes and promptly analyze the challenges associated with their biological applications. This will provide valuable perspectives on the potential of MOFs@PDA in clinical settings.